2012
DOI: 10.1093/infdis/jis027
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Associated CD16+56− Natural Killer Cell Interferon (IFN)–αR Expression Regulates Signaling and Is Implicated in IFN-α–Induced Hepatitis C Virus Decline

Abstract: IFN-αR expression on CD16(+)56(-) NK cells during chronic HCV infection may in part be genetically determined, and level of expression regulates IFN-α signaling, which in turn may contribute to control of HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…This is in line with the IFN-refractory state of nonresponders, who demonstrate a pre-activated IFN response signature in the liver, and minimal response to exogenous IFN-α treatment [124]. In support of these findings, higher baseline expression of the IFN-α receptor, IFNAR1, is associated with improved response to treatment, in an IFNL3 genotype-dependant manner [125]. Importantly, while nonresponders do not upregulate NKp30 or NKp46 in response to IFN treatment, responders demonstrate an increase in NKp30 or NKp46 following 12 weeks of treatment [96].…”
Section: Effect Of Pegylated Ifn-α/ribavirin-based Therapy On Nk Cellssupporting
confidence: 79%
“…This is in line with the IFN-refractory state of nonresponders, who demonstrate a pre-activated IFN response signature in the liver, and minimal response to exogenous IFN-α treatment [124]. In support of these findings, higher baseline expression of the IFN-α receptor, IFNAR1, is associated with improved response to treatment, in an IFNL3 genotype-dependant manner [125]. Importantly, while nonresponders do not upregulate NKp30 or NKp46 in response to IFN treatment, responders demonstrate an increase in NKp30 or NKp46 following 12 weeks of treatment [96].…”
Section: Effect Of Pegylated Ifn-α/ribavirin-based Therapy On Nk Cellssupporting
confidence: 79%
“…IFN‐αR is involved in anti‐HCV responses as noted by the positive association of its expression on NK cells and a favourable response to Peg‐IFN‐α/RBV . We show that in ART‐treated HIV/HCV co‐infection, a lower IFN‐αR expression may still indicate a lack of innate immune reconstitution by a sustained state of chronic NK activation with lower functionality.…”
Section: Discussionmentioning
confidence: 78%
“…A previous work has shown that both glyco- and protein-engineering lead to a higher binding affinity to CD16a. From a mechanistic point of view, these data suggest that this gain in affinity is achieved by different mechanisms ( 35 ), and it has also been shown that CD16a takes effect through several mechansisms ( 36 ). In the present study, we proved that CD16a was expressed in KCs, and we also investigated a profound action mechanism of ADCC in KCs for further.…”
Section: Discussionmentioning
confidence: 89%